Estudo químico e farmacológico in vitro e in silico de Senna Spp. Nativas do nordeste: Senna cana e Senna pendula - Monteiro, Jackelyne Alves (2018)
The knowledge of the chemical composition of higher plants has been the main objective of the study of the chemistry of natural products, since vast amount of botanical species remains without any chemical or pharmacological study, which makes difficult the rational use of botanical biodiversity. An important application of this use is the discovery of compounds from natural sources, potentially candidates for new drugs. This work reports the chemical and pharmacological study of two native species of the Northeastern flora, Senna cana I & B and Senna pendula I & B. The steps of the development of the work include tha dereplication by HPLC-DAD, the isolation and identification of substances from extracts of S. pendula, a proposal of methodology for optimization of the extraction of flavonoids, applied here, to S. fistula and S. obtusifolia, and the in silico study of the antimalarial potential of anthraquinones and flavonoids of Senna spp. The analysis of the results allowed the identification of 13 flavonoids in the two species studied, which were afterward quantified by HPLC-IES-MS. The chromatographic treatment of the hexane and ethanolic extracts of S. pendula made possible the isolation and identification of three triterpenes: frideline, α and β-amirin, and two flavonoids, epicatechin and quercetin. Structural elucidation was performed using spectroscopic techniques such as MS and NMR H1, C13 mono and bi-dimensional (HSQC). The biopharmacological potential of these species were also investigated by antioxidant activity, total phenolic and flavonoid content, anticholinesterase activity, larvicide against Aedes aegypti, toxicity against Artemia saline and inhibition of the angiotensin I converting enzyme (ACE). All reported substances are being registered for the first time in the species Senna cana and Senna pendula.